Redescription and systematic position of Diandongia pista from the Chengjiang Lagerstätte - Wang, Hai-Zhou; Zhang, Zhi-Fei; Holmer, Lars E.; Zhang, Zhi-Liang (Palaeoworld, 2023)
Diandongia pista Rong is the thickest-shelled and strongly mineralized of all the brachiopods that have been recorded from the Chengjiang Fauna. It is also one of the most common species in the biota. Previous accounts have concentrated largely on the exceptionally preserved soft-bodied anatomy of this species. Here its detailed internal and external shell morphologies are described for the first time, based on BSEM and SEM observations. Its general shell morphology, pseudointerareas, and pustulose ornamentation are most similar to those of the Botsfordiidae, where many species have a Diandongia-like rhombic pattern of pustules in the juvenile apical region only. On the other hand, other aspects of the muscle pattern and the partly smooth adult ornamentation of D. pista is more suggestive of species within the Neobolidae, like Edreja. The mantle canal system in sub-adults of D. pista is comparable to that of the Eoobolidae and Obolidae, whereas the adult vascular system branches peripherally in dichotomy. D. pista may be the earliest representatives possessing some plesiomorphic characters of the Botsfordiidae.